Analysis Of Information System Service Quality In Motor Vehicle Inspection Using The PIECES Framework - Muhammad Adil Hakim; Qadhli Jafar Adrian (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to evaluate the quality of information system services in motor vehicle testing services at the Department of Transportation of Bandar Lampung City using the PIECES Framework approach. The background of this research is based on the increasing public demand for effective, efficient, and transparent public services, particularly in periodic motor vehicle testing (Uji KIR), which plays a strategic role in ensuring transportation safety. The research data were obtained from the 2026 Community Satisfaction Survey (SKM) involving 500 respondents. The results indicate that the Community Satisfaction Index (CSI) score is 76.64, which falls into the “Good” category. However, the analysis reveals several operational issues, including relatively long service waiting times, suboptimal effectiveness of the calling system, and limitations in supporting facilities and infrastructure. Through the PIECES approach, which includes Performance, Information, Economy , Control, Efficiency, and Service aspects, the findings indicate that Performance, Efficiency, and Service are the most influential dimensions affecting the quality of information system services. Therefore, improvements are required in queue management systems, enhancement of information delivery quality, and strengthening of service infrastructure. This study is expected to provide both conceptual and practical contributions to improving the quality of information system services in the public service sector.